Recent Progress on the Performance of Lead‐Based Halide Perovskite APbX3 Detectors. Issue 9 (16th March 2022) - Chen, Yanhong; Feng, Zhenjie; Pal, Arnab; Zhang, Jincang
Abstract : Lead‐based halide perovskites APbX3 are likely to become competitive candidates in applications of photodetectors and X/γ‐ray detectors owing to their excellent optical and electrical characteristics, such as high and balanced carrier mobility, long carrier diffusion length, and adjustable bandgap. Based on this system, the article summarizes the performance parameters, such as responsivity, detectivity, external quantum efficiency, and response time of photodetector, and generalizes the research status of its application in near‐infrared light, visible light, and ultraviolet light photodetectors. In addition to that, it also summarizes the recent progress of X/γ‐ray detectors. What is more, the influence of radii of A‐site cations on the photoelectric performance are discussed. Finally, based on these summary and discussion, a research trend could be raised that more and more researchers tend to fabricate APbX3 perovskite with single‐crystalline thin‐film for high‐performance photodetectors in the future. It is proposed that if the A‐site ion is an organic group with a larger radius than the formamidinium (FA + ), it may have better photoelectric properties than FAPbX3 . Inorganic lead‐based perovskite single crystals with few defects, fast carrier mobility, and good stability are beneficial for attaining low dose rate and high‐energy resolution X/γ‐ray detectors. Abstract : This review summarizes the photodetectors' performance parameters and the X/γ‐ray detectors' recent progress of the lead‐based halide perovskite APbX3 system. The research results of near‐infrared‐ultraviolet light devices are analyzed, the mechanism of the good photoelectric properties of FAPbX3 photodetectors is discussed, as well as several important outlooks for future research are proposed.